Functional Analysis of Arabidopsis Postprenylation CaaX Processing Enzymes and Their Function in Subcellular Protein Targeting - Bracha-Drori, Keren (American Society of Plant Biologists, 2008)
Prenylation is a posttranslational protein modification essential for developmental processes and response to abscisic acid. Following prenylation, the three C-terminal residues are proteoliticaly removed and in turn the free carboxyl group of the isoprenyl cysteine is methylated. The proteolysis and methylation, collectively referred to as CaaX processing, are catalyzed by Ste24 endoprotease or Rce1 endoprotease and by an isoprenyl cysteine methyltransferase (ICMT). Arabidopsis (Arabidopsis thaliana) contains single STE24 and RCE1 and two ICMT homologs. Here we show that in yeast (Saccharomyces cerevisiae) AtRCE1 promoted a-mating factor secretion and membrane localization of a ROP GTPase. Furthermore, green fluorescent protein fusion proteins of AtSTE24, AtRCE1, AtICMTA, and AtICMTB are colocalized in the endoplasmic reticulum, indicating that prenylated proteins reach this compartment and that CaaX processing is likely required for subcellular targeting. AtICMTB can process yeast a-factor more efficiently than AtICMTA. Sequence and mutational analyses revealed that the higher activity AtICMTB is conferred by five residues, which are conserved between yeast Ste14p, human ICMT, and AtICMTB but not in AtICMTA. Quantitative real-time reverse transcription-polymerase chain reaction and microarray data show that AtICMTA expression is significantly lower compared to AtICMTB. AtICMTA null mutants have a wild-type phenotype, indicating that its function is redundant. However, AtICMT RNAi lines had fasciated inflorescence stems, altered phylotaxis, and developed multiple buds without stem elongation. The phenotype of the ICMT RNAi lines is similar to farnesyltransferase β-subunit mutant enhanced response to abscisic acid2 but is more subtle. Collectively, the data suggest that AtICMTB is likely the major ICMT and that methylation modulates activity of prenylated proteins.